Penguatan Literasi Wisata Budaya Madura dalam Pembelajaran Bahasa Indonesia melalui Pengaktualan Kuliner Pulau Mandangin sebagai Pendukung Pembelajaran di Era Merdeka Belajar - Fiyan Ilman Faqih; Arief Setyawan (Tadris Bahasa Indonesia, Fakultas Tarbiyah, Institut Agama Islam Negeri Madura, 2022)
Madura has various types of tourism, namely religious, marine, and cultural tourism. One of the cultural tourism in Madura is culinary. There are many culinary tours that must be tried by local, domestic, or foreign tourists. Culinary on the island of Mandangin can be an attraction for local, domestic and foreign tourists. This research is a development research using the Plomp development model. One of the stages, namely the preliminary research stage, is one of the initial stages that must be carried out in development research. Based on the results of interviews, educators have never created or developed reading materials for students. Based on the results of observations about culinary on the island of Mandangin, there are various kinds of typical Mandangin culinary. The culinary specialties of Mandangin Island are saop, nase 'segah, skipjack fish paste, Le'-Pale', Rojek Kottok, Tajhin Sapar, and others. The actualization of culinary tourism in Mandangin needs to be done because Mandangin Island has many other tourism potentials. The actualization of culinary tourism potential in Mandangin will be able to develop other tourism potentials. This happens because every tourism potential in Mandangin goes hand in hand. The form of reading material will be in the form of short stories and drama scripts about the culinary arts of Mandangin Island. Therefore, it is important to develop reading materials about culinary as a form of actualizing Mandangin island culinary as a supporter in the era of independent learning.